Factors Affecting the Event of Anemia in Pregnant Women Trimester III in Puskesmas Namorambe Districts Deli Serdang Year 2022 - Nurainun; Basaria Manurung; Kurniani; Arni; Surati (Institute of Computer Science (IOCS), 2022)
Injectable contraception is a way to prevent pregnancy by means of hormonal injections, this type of hormonal contraceptive injection in Indonesia is increasingly being used, the more it is used because of its effective work, practical use, relatively cheap and safe price. This study aims to determine the relationship between the use of 3-month injectable family planning and weight gain in women of childbearing age at the Maga Health Center, Mandailing Natal Regency in 2022.This type of research is an analytical survey with a cross sectional approach. The population is all pregnant women who are at the Maga Health Center, Mandailing Natal Regency in 2022, totaling 36 pregnant women. The number of samples used is 52 people obtained by using purposive sampling technique. Data analysis technique using chi square.The results obtained in this study were from 52 respondents, there was a relationship between the knowledge variable and weight gain with a p value = 0.001, there was a relationship between the variable length of use and weight gain with a p value = 0.002, there was a relationship between the age variable and weight gain body with a value of p = 0.002, there is a relationship between the education variable and weight gain with a p value = 0.003 and there is a relationship between the work variable and weight gain with a p value = 0.001. there is a relationship between the knowledge variable and weight gain, there is a relationship between the variable duration of use and weight gain, there is a relationship between the age variable and weight gain, there is a relationship between the education variable and weight gain and there is a relationship between the work variable and the increase weight. It is suggested to the puskesmas to increase the knowledge of mothers to increase counseling related to the use of injectable contraception.